The winning strategy of the sj4000 business - Rasyid, Muhammad; Permadi Iskandar, Budi (The Indonesian Journal of Business Administration, 2016)
Abstract- SJ4000 Indonesia is a camera shop that sells SJ4000 Indonesia is selling a small camera that aimed at the adventurous or those who loved sports and diving activities, cycling, hiking and even only used for normal photos. Founded by Muhammad Rasyid because it began with the desire to have a small camera that can be possessed in all conditions but the price is very expensive, then he was looking for another alternative. On marketing of SJ4000 Indonesia found there was a problem. Spreading the marketing through Indonesia can be said very traditionally that only using word of mouth and also offer to closet friends. On stock management, SJ4000 Indonesia found the problem like donâ€™t know what model that should be taken more to sell and how many stocks that should be sold. The owner wants to expand his business and wants the product will be known through social media and online shopping which are a trend nowadays for the people of Indonesia. SJ4000 Indonesia chose Alibaba as a vendor, shipping using Konghai Express and as well as the method of payment, a marketing strategy using the Facebook Ads, and invites resellers to do the business in SJ4000 Indonesia and also makes a good service to resellers and consumers by using securing position. In the end SJ4000 Indonesia managed to declare that the use of social media marketing is very effective and easy. The owner of SJ4000 Indonesia decided to become a distributor due to the sale of competitors are unreasonable. Â Keyword: marketing strategy, online business, risk management